Start project management from Scratch in an ICT department of a public higher education organization: How to manage change? - Rodrigues, M. C.; Domingues, L.; Oliveira, J. P. (22ª Conferência da Associação Portuguesa de Sistemas de Informação (CAPSI 2022), 2022)
The 7th edition of the PMBOK extols stakeholder involvement and acceptance of change as crucial management principles to ensure good project outcomes, as engaged people produce more and better, become more open and flexible to embrace the changes inherent in the project context. From a single case study, the initiation of project management functions in a public organization in the education sector is discussed. The value of this article lies in the connection between theory and practice, as it brings Anderson and Kotter's guidelines applied during an actual project, revealing the benefits and difficulties faced in leveraging and maintaining stakeholder engagement. As a result, it affirms the importance of context analysis to design and conduct changes in the environment where the project takes place, and of breaking the forces of inertia to foster experimentation and gradual improvements in the teams' work dynamics.